2006
DOI: 10.1007/11821069_29
|View full text |Cite
|
Sign up to set email alerts
|

Smart Robot Teams Exploring Sparse Trees

Abstract: We consider a tree which has to be completely explored by a group of k robots, initially placed at the root. The robots are mobile and can communicate using radio devices, but the communication range is bounded. They decide based on local, partial knowledge, and exchange information gathered during the exploration. There is no central authority which knows the graph and could control the movements of the robots-they have to organize themselves and jointly explore the tree. The problem is that at every point of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…We look at the case of larger groups of agents, for which D is the dominant factor in this lower bound. This complements previous research on the topic for trees [6,8] and grids [17], which usually focused on the case of small groups of agents (when n/k is dominant).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…We look at the case of larger groups of agents, for which D is the dominant factor in this lower bound. This complements previous research on the topic for trees [6,8] and grids [17], which usually focused on the case of small groups of agents (when n/k is dominant).…”
Section: Introductionsupporting
confidence: 68%
“…In [13] authors show that the competitive ratio of the strategy presented in [8] is precisely k/ log k. Another DFS-based algorithm, given in [2], has an exploration time of O(n/k+D k−1 ) time steps, which provides an improvement only for graphs of small diameter and small teams of agents, k = O(log D n). For a special subclass of trees called sparse trees, [6] introduces online strategies with a competitive ratio of O(D 1−1/p ), where p is the density of the tree as defined in that work. The best currently known lower bound is much lower: in [7], it is shown that any deterministic exploration strategy with k < √ n has a competitive ratio of Ω(log k/ log log k), even in the global communication model.…”
Section: Related Workmentioning
confidence: 99%
“…For a given graph with n nodes, n robot collaborative exploration [12,19,13,5,6,20,11] asks that these robots coordinate amongst each other and collectively visit every node of the graph at least once. Notice that any solution to dispersion immediately applies to n robot collaborative exploration for the same assumptions and model parameters.…”
Section: Background and Motivationmentioning
confidence: 99%
“…In particular, on trees the problem of exploring all vertices is equivalent to exploring all edges. Apart from the aforementioned previous work on our problem in planar graphs [23] and cycles [2,25], it has been studied on un-weighted trees also for multiple synchronously moving searchers [13,14,17].…”
Section: Introductionmentioning
confidence: 99%